Influence of residue and nitrogen fertilizer additions on carbon mineralization in soils with different texture and cropping histories. - Xianni Chen; Xudong Wang; Matt Liebman; Michel Cavigelli; Michelle Wander (PLoS ONE, 2014)
To improve our ability to predict SOC mineralization response to residue and N additions in soils with different inherent and dynamic organic matter properties, a 330-day incubation was conducted using samples from two long-term experiments (clay loam Mollisols in Iowa [IAsoil] and silt loam Ultisols in Maryland [MDsoil]) comparing conventional grain systems (Conv) amended with inorganic fertilizers with 3 yr (Med) and longer (Long), more diverse cropping systems amended with manure. A double exponential model was used to estimate the size (Ca, Cs) and decay rates (ka, ks) of active and slow C pools which we compared with total particulate organic matter (POM) and occluded-POM (OPOM). The high-SOC IAsoil containing highly active smectite clays maintained smaller labile pools and higher decay rates than the low-SOC MDsoil containing semi-active kaolinitic clays. Net SOC loss was greater (2.6 g kg(-1); 8.6%) from the IAsoil than the MDsoil (0.9 g kg(-1), 6.3%); fractions and coefficients suggest losses were principally from IAsoil's resistant pool. Cropping history did not alter SOC pool size or decay rates in IAsoil where rotation-based differences in OPOM-C were small. In MDsoil, use of diversified rotations and manure increased ka by 32% and ks by 46% compared to Conv; differences mirrored in POM- and OPOM-C contents. Residue addition prompted greater increases in Ca (340% vs 230%) and Cs (38% vs 21%) and decreases in ka (58% vs 9%) in IAsoil than MDsoil. Reduced losses of SOC from residue-amended MDsoil were associated with increased OPOM-C. Nitrogen addition dampened CO2-C release. Clay type and C saturation dominated the IAsoil's response to external inputs and made labile and stable fractions more vulnerable to decay. Trends in OPOM suggest aggregate protection influences C turnover in the low active MDsoil. Clay charge and OPOM-C contents were better predictors of soil C dynamics than clay or POM-C contents.